Tumor-Targeted Gene Silencing IDO Synergizes PTT-Induced Apoptosis and Enhances Anti-tumor Immunity - Zhang, Yujuan; Feng, Yuanyuan; Huang, Yanqing; Wang, Yifan; Qiu, Li; Liu, Yanling; Peng, Shanshan; Li, Rong; Kuang, Nanzhen; Shi, Qiaofa; Shi, Yanmei; Chen, Yiguo; et al. (Frontiers in Immunology, 2020)
Background: Photothermal therapy (PTT) has been demonstrated to be a promising cancer treatment approach because it can be modulated to induce apoptosis instead of necrosis via adjusting irradiation conditions. Recently, an abscopal anti-tumor immunity has been highlighted, in which PTT on the primary tumor also induced repression of distant tumors. In PTT cancer treatments, the mechanism and the role of immune checkpoints to enhance anti-tumor immunity needs to be investigated. Methods: We prepared a multi-functional gold nanorod reagent, GMPF-siIDO, that is composed of gold nanorods (GNRs) that act as the nano-platform and photothermal sensitizer; folic acid (FA) as the tumor-targeting moiety; and IDO-specific RNA (siIDO) as an immune-stimulator functionality for inducing anti-tumor immunity. For this study, we adjusted the irradiation condition of PTT to induce apoptosis and to silence the immune checkpoint indoleamine 2,3 dioxygeonase (IDO), simultaneously. Results: Our studies provide evidence that photothermal effects kill tumor cells mainly via inducing apoptosis, which can significantly improve antitumor immunity when IDO was down-regulated in TME through significant increases of localized CD8+ and CD4+ lymphocytes in tumor tissue, the downregulation of CD8+ and CD4+ lymphocyte apoptosis, and the upregulation of antitumor cytokines, TNF-α and IFN-γ. Conclusion: In this study, we, for the first time, validated the role of IDO as a negative regulator for both PTT-induced tumor cell apoptosis and anti-tumor immunity; IDO is a critical immune checkpoint that impedes PTT while combination of gene knockdown of IDO in TME enhances anti-tumor efficacy of PTT.